TOWARDS EDUCATION 2050: METHODOLOGICAL OBSERVATIONS - Ahrens, Andreas; Zascerinska, Jelena; Bikova, Anastasija; Zascerinskis, Mihails (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2024)
Education 2050 is a determining factor of Future 2050. Therefore, different attempts to envision Education 2050 have been undertaken, and their results have been presented to the wider public. However, the scientific view on Education 2050 is under-represented, and the methodology of envisaging Education 2050 remains under-explored. The aim of this paper is to analyse methodologies applied to the projection of Education 2050. The exploratory research is employed in this work. Data were collected via observations and processed via content analysis. Findings were structured, summarized and compared, and allowed concluding that the use of methodologies in the works selected for analysis of Education 2050 is fragmentary. Only some methodology’s elements are leveraged for shaping Education 2050 in the analysed works. The aspect of Information and Communication Technologies prevails in projecting Education 2050 in the works available for analysis. The analysed works have more differences than similarities in the use of methodological elements related to the design of Education 2050. A new research question has been formulated: What is a methodology for envisioning Education 2050? Limitations of the research have been presented. Further work has been proposed.